1970
DOI: 10.3126/njst.v11i0.4132
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Dynamics in Treeline Ecotone of Langtang National Park, Central Nepal

Abstract: A study was carried out at the treeline ecotone (3,730m-3,950m asl) of Langtang National Park in central Nepal with an aim to document the impact of climatic warming on ecological chracteristics. Three sampling sites were selected at Chaurikharka and Lauribina, where no serious anthropogenic pressure was noticed. The nearest meteorological station has records of climatic warming in recent years. Six tree species and three shrub species belonging to seven families were enumerated from the study plots. The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
1
9
2
Order By: Relevance
“…Lower belt of the forest was occupied by Abies spectabilis and Larix himalaica in our study site but in the dry Manang valley, central Nepal, lower belt was dominated by Abies spectabilis and Pinus wallichiana Lekhak 2007, Shrestha et al 2007). In a study, Gaire et al (2010) recorded six tree species from treeline ecotone of Langtang National Park, which is greater than our observation from Himalayan treeline.…”
Section: Community Structurecontrasting
confidence: 50%
“…Lower belt of the forest was occupied by Abies spectabilis and Larix himalaica in our study site but in the dry Manang valley, central Nepal, lower belt was dominated by Abies spectabilis and Pinus wallichiana Lekhak 2007, Shrestha et al 2007). In a study, Gaire et al (2010) recorded six tree species from treeline ecotone of Langtang National Park, which is greater than our observation from Himalayan treeline.…”
Section: Community Structurecontrasting
confidence: 50%
“…Based on size class structure, the woody species can demonstrate three types of regeneration: unimodal, sporadic, and inversely J-shaped (Wangda and Ohshwa 2006). Gaire et al (2010) observed an inversely J-shaped size class distribution in the treeline ecotone of Langtang National Park. Maren et al (2015) found almost similar regeneration condition based on the dbh class distribution (inversely J-shaped) of Pinus wallichiana and Juniperus indica in the forests situated on the north and the south-facing slopes in the Manang Valley.…”
Section: Resultsmentioning
confidence: 82%
“…The currently recorded tree density at the upper site was found to be both higher as well as lower than the one recorded in some other studies in the Himalayan region. Gaire et al (2010) found the average tree density of 734 stem/ha and the average basal area of 20.56 m 2 /ha in the treeline ecotone of Langtang National Park. In another study, Bhuju et al (2010) recorded a density of 445 stems/ha and total basal area of 11.2 m 2 /ha from the treeline region while a density of 1,034 stems/ha and a basal area of 18.6 m 2 /ha from the treeline region of the Sagarmatha National Park.…”
Section: Resultsmentioning
confidence: 89%
“…Forests that have a bell-shaped DBH distribution lack old and young trees [81][82][83]. Therefore, such forests are unsustainable and reflect population decline caused by external disturbances [84,85]. An inverse J-shaped DBH distribution appears because of high initial mortality of young trees [85].…”
Section: Discussionmentioning
confidence: 99%